Entrepreneurship Training for Students at Raudhatunnasyiin Boarding School, Banjarbaru - Rusdiana, Rusdiana (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2023)
Article (PKM) is motivated by the existence of the Raudhatul Muhibbin Islamic Boarding School Foundation which aims to provide a concrete understanding of the concept of entrepreneurship so that the students of the Raudhatul Muhibbin Islamic Boarding School Foundation can develop their economy better. The method used in this PKM article is a field study by directly giving directions to the students of the Raudhatul Muhibbin Islamic Boarding School Foundation while the source of data is through observation, interviews and documentation. The results of this PKM are, first, the students of the Raudhatul Muhibbin Islamic Boarding School Foundation understand more about the concept of entrepreneurship that is in accordance with Islam. Second, the students of the Raudhatul Muhibbin Islamic Boarding School Foundation can practice entrepreneurial strategies according to Islamic concepts